You need the more relaxed side, but you also need the adrenaline: promoting physical health as perceived by youth with vision impairment. Issue 6 (12th March 2020) - Anderson, Ross; Warren, Narelle; Misajon, RoseAnne; Lee, Stuart
Abstract: Purpose: Within a larger investigation of their conceptualizations of wellbeing, this article explores elements of physical health discussed by youth with vision impairment (VI) to inform physical health programs, with youths' personal motivation to be physically active previously identified as key to participation. Methods: Twenty-one youth (aged 12–25) participated. The qualitative data discussed was collected for each participant across three interviews/focus groups and audio-recording tasks in a project regarding their conceptualizations of wellbeing. Results: Thematic analysis identified an understanding of physical health characterized by four subthemes. First, participants' bodily health and fitness produced positive self-perceptions, but also held greater importance given the increased physical risks of living with VI. Second, energy—a positive, motivating feeling—held additional salience given extra demands upon participants related to their VIs. Thus, relaxation strategies (e.g., reading) were essential to meet these demands and recover from injury/pain (bodily health). Meanwhile, physical activity promoted fitness and vitality. Specific activities also entailed freedom of movement, contrasting heightened environmental risks in other settings. Conclusions: To better align with possible participation motivators, participants' discussions suggested that programs should target relaxation and energy in youth with VI—alongside physical activity—and offer free and safe movement in space. Implications for Rehabilitation: Youth with vision impairment consider feelings of energy important to their physical health, alongside their bodily health and fitness. Physical health programs for youth with vision impairment should target both physical activity and relaxation. Youth with vision impairment report greater physical and social threats to their bodily safety in considering their bodily health. Physical health programs for youth with vision impairment should provide an opportunity for free movement in space to balance these lived physical risks.